Value at risk for the term structure of interest rates : an orthogonal approach (2006)
Value at Risk is the maximum potential loss of a portfolio with a given probability during a period of time. This tool is extremely useful for hedging portfolio decisions as making efficient strategies by controlling for the incremental risk. The principal challenge of this risk measure is the accuracy of the loss estimation which depends on the particular model used. In this sense, the main objective of this paper is to present an adequate methodology in order to measure market risk for fixed income portfolios. It evaluates risk related to the yield curve in time by using Principal Components Analysis, Orthogonal Garch and Key Rates Durations. Using dynamic conditional correlations as the simulation under stress scenarios let ensure a Value at Risk. Models output generate dynamic hedging strategies as portfolio management in a coherent way fitting positions taken in the market.